Biochemical polymorphism of several local breeds and cross breeds - Zafer Bulut; Mehmet Nizamlıoğlu; Vahdettin Altunok; İnci Togan; Firuze Kurtoğlu; M.Emin Tekin; Ali Ergin (Eurasian Journal of Veterinary Sciences)
In the study to determine the genetic structure of local breeds and cross breeds of sheep, glutamate oxaloacetate transaminase (GOT) and phosphogluconate dehydrogenase (PGD) enzyme loci were examined by starch gel electrophoresis. In the present study, the red cell enzymes of 250 local breeds and cross breeds of sheep from Konya Central Animal Research Institute were used. For each of the enzyme systems appropriate buffers and chemical for the activity staining were used in accordance with the information given in the literature. The observed bands of the izoenzymes were analysed. For the enzyme loci Got and Pgd neither the individuals of local breeds of sheep nor the individuals of cross breeds of sheep exhibited any variation. They displayed identical bands and they were all homozygotes. This study explained that two enzyme systems exhibited monomorphic. It seem that, with respect to the loci studied, cross breeds of sheep do not differ from the local breeds of sheep.